2022
DOI: 10.1016/j.contraception.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

“I just was really scared, because it's already such an uncertain time”: Exploring women's abortion experiences during the COVID-19 pandemic in Canada

Abstract: I just was really scared, because it's already such an uncertain time": Exploring women's abortion experiences during the COVID-19 pandemic in Canada, Contraception (2022), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…These findings add to emerging literature about the impact of the pandemic on abortion care by highlighting the increasingly complex process individuals navigated in the first year of the pandemic. EOs deeming abortion as non-essential likely intensified challenges, as accessing abortion even in less restrictive environments was increasingly complex due to public health-related responses [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings add to emerging literature about the impact of the pandemic on abortion care by highlighting the increasingly complex process individuals navigated in the first year of the pandemic. EOs deeming abortion as non-essential likely intensified challenges, as accessing abortion even in less restrictive environments was increasingly complex due to public health-related responses [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have shown how both EOs and the COVID-19 pandemic affected abortion provision in the U.S and other Global North countries [ 10 , 11 , 12 , 13 , 14 ]. A survey of independent abortion facilities found EOs significantly disrupted services, and roughly 70% of independent facilities in states that deemed abortion “non-essential” temporarily closed, canceled, or postponed services [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The Indigenous people who participated in this study put forward practical solutions for improving access to and experiences with abortion services in Canada. While recommendations for increased support, accessibility, availability, comfortability, and awareness have been highlighted in other Canadian abortion literature, 7 , 9 , 33 , 34 Indigenous voices and experiences have yet to be heard. 11 Like other Canadian studies, Indigenous participants in our study spoke to the need for abortion access supports, including help with appointment bookings, travel, advocacy during appointments, and/ or post-abortion support.…”
Section: Discussionmentioning
confidence: 99%
“…12,21 The COVID-19 pandemic has also complicated abortion care in Canada and created additional challenges for some abortion seekers to navigate. 22 Although the federal government reaffirmed in March 2020 that abortion care is an essential medical service 23 temporary clinic closures and local, inter-provincial, and international travel restrictions impacted access to facility-based abortion services, particularly at later gestational ages. 24,25 Both the National Abortion Federation (NAF) Canada and Action Canada for Sexual Health and Rights (Action Canada) operate hotlines that provide information, financial support, and travel assistance to people seeking abortion care.…”
Section: Introductionmentioning
confidence: 99%
“…Some abortion seekers also need financial support to cover the costs associated with the procedure or associated travel 12,21 . The COVID‐19 pandemic has also complicated abortion care in Canada and created additional challenges for some abortion seekers to navigate 22 . Although the federal government reaffirmed in March 2020 that abortion care is an essential medical service 23 temporary clinic closures and local, inter‐provincial, and international travel restrictions impacted access to facility‐based abortion services, particularly at later gestational ages 24,25…”
Section: Introductionmentioning
confidence: 99%